107k views
4 votes
Please help me!! thank you

Please help me!! thank you-example-1

2 Answers

4 votes

Answer:

-6 0 3 and 7 (2nd answer, 4th answer, 5th answer, and last answer.)

Explanation:

Just replace "x" with the numbers below individually.

To make it faster don't forget that multiplying anything times 0 = 0

:)

User Ryan Erdmann
by
5.7k points
6 votes

Answer:

x =0 x=3 x=-6 x=7

Explanation:

x (x-3) (x +6 ) (x -7 ) =0

Using the zero product property

x =0 x-3=0 x+6=0 x-7 =0

x =0 x=3 x=-6 x=7

These are the zeros

User Kevin Kreps
by
5.3k points